A Strengthening the Institutionalization of Coconut Sugar Tapper Farmers (Case Study of Panusupan Village, Cilongok District, Banyumas Regency): Strengthening the Institutionalization of Coconut Sugar Tapper Farmers (Case Study of Panusupan Village, Cilongok District, Banyumas Regency) - Nurin Aulia Nurin (Universitas Medan Area, 2026)
This study aims to analyze the institutional structure of coconut sugar tappers in Panusupan Village, Cilongok District, Banyumas Regency, using Paulo Freire's empowerment theory perspective. The research approach employed a qualitative case study method through in-depth interviews, participant observation, and documentation studies. The results indicate that the institutional structure of coconut sugar tappers remains traditional and has not fully transformed into a critical empowerment tool. Institutional strengthening needs to be directed at awareness-raising, participatory dialogue, and collective action to enable coconut sugar tappers to improve their bargaining power and economic independence. Keywords: farmer institutions, tappers, coconut sugar, empowerment, Paulo Freire.